2020
DOI: 10.1002/adfm.202070234
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid Electrolytes: Safe, Stable Cycling of Lithium Metal Batteries with Low‐Viscosity, Fire‐Retardant Locally Concentrated Ionic Liquid Electrolytes (Adv. Funct. Mater. 35/2020)

Abstract: In article number 2003132, Hochun Lee and co‐workers design a locally concentrated ionic liquid electrolyte with a non‐solvating, fire‐retardant hydrofluoroether that can resolve the chronic viscosity problems of ionic liquid electrolytes, while further strengthening their intrinsic benefits to establish safe, stable Li metal batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many strategies have also been widely employed to prepare advanced batteries with higher specific capacity and higher safety. Lee et al reported a fire-retardant locally concentrated ionic liquid (LCIL) electrolyte, which exhibited high ionic conductivity and low viscosity, apparent lithium-ion transference number ( t Li+ ), self-diffusion coefficients, and separator wettability. Besides, the Li//LiCoO 2 cells with LCIL also showed excellent cycle capability and rate charge/discharge performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many strategies have also been widely employed to prepare advanced batteries with higher specific capacity and higher safety. Lee et al reported a fire-retardant locally concentrated ionic liquid (LCIL) electrolyte, which exhibited high ionic conductivity and low viscosity, apparent lithium-ion transference number ( t Li+ ), self-diffusion coefficients, and separator wettability. Besides, the Li//LiCoO 2 cells with LCIL also showed excellent cycle capability and rate charge/discharge performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ionic liquids (ILs) have been investigated as polymerization catalysts/initiators of ε-caprolactone (εCL), ε-caprolactam, and epoxy resins. ILs are organic salts whose melting point is below 100 °C; indeed, many are liquids at room temperature. , IL molecules usually consist of a cationic “head” with an anionic counterion and one or more hydrophobic (aliphatic and/or aromatic) “tails.” Depending on the type of cationic core, the size and type of the counterion, the length of aliphatic alkyl chain(s), or a combination of alkyl chains with aromatic structures, ILs exhibit several intrinsic properties such as low volatility, high thermal and chemical stability, insignificant flammability, good thermal conductivity, high ionic mobility, stability in the presence of moisture, etc. Mainly thanks to beneficially high thermal stability and tuneable chemical structures, ILs have a huge potential for applications in the field of polymers, e.g., as initiators of polymerization, catalysts, curing agents, , or building blocks of polymer networks. , However, the high viscosity of ILs and their difficult separation from the products are the main limitations of their wider use in polymer catalysis …”
Section: Introductionmentioning
confidence: 99%